PERANAN KEPALA DESA DALAM PELAYANAN PUBLIK (Studi di Desa Pontak Kabupaten Minahasa Selatan) - Potabuga, Jamin (ACTA DIURNA KOMUNIKASI, 2015)
Service of public have the character of to serve without exception public interest which passing role of government is not private sector. Through role of available government of goods property of public which is later; then used to serve common interest. Countryside head of pontak assessed to succeed in service of north in Sulawesi. Public whereas most countrysides assessed by less below the mark in service of public. Role of countryside head of pontak can become example of, its him conception what its it so that succeed?. According to countryside head of Pontak (Old Law of Pontak) (countryside head in Minahasa referred as "old law". Efficacy of governance of democracy determined by desire realize common interest become intention and intention before chosen as government. After chosen round up our intention and intention and act as government of best choice of people, (this opinion is processed from result of circumstantial interview with old law of countryside of Pontak so called of Mody Rawis). Result of this research indicate that efficacy of chosen government in service of public determined by there is do not it intention and intention realize common interest before chosen become government. Proven truth, Johanes Montolalu countryside elite figure sorang of Pontak as informan lock in this research explain that Mody Rawis before chosen as old law it is true have been long enough impetous play a part in business of kemasyaratan development and, he is biggest contributor of development of countryside hall and church, arch, walke plantation. He it is true good fellow, diligent and smart, hence chosen him him again at second period as old law is this countryside. Our countryside there is make up of development like now of role of countryside head of Mody Rawis, he is its people serve society non served, all administrative services quickly and precisely do not be procrastinated. Regent spell out members in its oration when coming delivering appreciation star to old law, that only countryside of Pontak complete countryside office facilities and basic facilities is sub-province of South Minahasa, and responsibility reporting lead countryside per annum best diterimah and clear of KKN. Is there by found by concept intention and intention of before" be that of elementary think used by countryside head of Pontak so that succeed in service of public. Keywords: Intention and Intention Before Abstrak Pelayanan publik bersifat melayani kepentingan umum tanpa kecuali yang melalui peranan pemerintah bukan swasta. Dengan melalui peranan pemerintah tersedia barang milik publik yang kemudian digunakan untuk melayani kepentingan bersama. Kepala Desa Pontak dinilai berhasil dalam pelayanan publik di Sulawesi Utara sementara sebagian besar desa-desa dinilai kurang di bawah standar dalam pelayanan publik. Peranan kepala Desa Pontak dapat menjadi contoh, pertanyaanya konsep apa yang digunakanya sehingga berhasil?. Menurut kepala Desa Pontak (Hukum Tua Pontak) (kepala desa di Minahasa disebut â€œhukum tuaâ€). Keberhasilan pemerintahan demokrasi ditentukan oleh keinginan mewujudkan kepentingan bersama menjadi niat dan tekat sebelum terpilih sebagai pemerintah. Setelah terpilih bulatkan niat dan tekat kita dan bertindak sebagai pemerintah pilihan terbaik rakyat, (pendapat ini diolah dari hasil wawancara mendalam dengan hukum tua Desa Pontak bernama Mody Rawis). Hasil penelitian ini menunjukkan bahwa keberhasilan pemerintah terpilih dalam pelayanan publik ditentukan oleh ada tidaknya niat dan tekad mewujudkan kepentingan bersama sebelum terpilih menjadi pemerintah. Kebenaran terbukti, Johanes Montolalu sorang tokoh masyarakat Desa Pontak sebagai informan kunci dalam penelitian ini menjelaskan bahwa Mody Rawis sebelum terpilih sebagai hukum tua memang sudah lama giat berperan dalam urusan kemasyaratan dan pembangunan, dia penyumbang terbesar pembangunan gereja dan balai desa, gapura, jalan perkebunan. Dia memang orang baik, cerdas dan rajin, makanya dia terpilih lagi pada periode yang kedua sebagai hukum tua di desa ini. Desa kami ada peningkatan pembangunan seperti sekarang atas peranan kepala desa Mody Rawis, dia orangnya melayani masyarakat bukan dilayani, semua pelayanan administrasi cepat dan tepat tidak ditunda-tunda. Bupati bilang dalam pidatonya pada waktu datang menyerahkan bintang penghargaan kepada hukum tua, bahwa hanya di Desa Pontak sarana dan prasarana kantor desa terlengkap di Kabupaten Minahasa Selatan, dan laporan pertanggungjawaban kepala desa tiap tahun diterima terbaik dan bersih dari KKN. Dengan demikian ditemukan konsep â€œniat dan tekad sebelumâ€ sebagai dasar berpikir yang digunakan oleh kepala Desa Pontak sehingga berhasil dalam pelayanan publik. Kata Kunci : Niat dan tekad sebelum.